Physiological Supply of Main Nutrients of Pregnant Women in The Southern Regions of The Republic of Uzbekistan - Kurbanov Shaniyaz Kurbanovich; Buranova Gulnoza Boymuratovna (European Science Publishing, 2023)
This article is devoted to the study of macronutrients and their energy value in the daily food intake of pregnant women aged 18-29 and 30-39 years living in rural conditions of Kashkadarya region. According to the obtained results, the amount of protein in the daily diet of the subjects was relatively low and carbohydrates in the diet was close to or significantly above the norm.
Keywords: ration, proteins, fats, carbohydrates, energetic value, trimester.